HUBUNGAN PERILAKU KADARZI DENGAN STATUS GIZI BALITAUSIA 12-59 BULAN DI WILAYAH KERJA PUSKESMAS BLANGKEJEREN KECAMATAN BLANGKEJEREN KABUPATEN GAYO LUES TAHUN 2012 - Ega Karolina; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
The nutritional behavior of mother that consist of knowledge, attitude and action in the daily activities influence the nutrition status of the child. KADARZI is a family which have a balance nutrition behavior, understand the nutrition problem and can solve the nutrition problem for household. The study is aimed to know the relationship between KADARZI behavior with nutritional status of the children in age of 12-59 months. This research is an analytic survey using cross sectional design. The population is all mother of children by simple random sampling as 106 people. The primary data was collected by observation and direct interview to the respondent and the secondary data from community health center and statistical data from district office of Blangkejeren. The results of this study showed that (67,9%) of the mother had medium knowledge, had good attitude (60,7%).The household had to be the KADARZI as many as (16,0%). The result of statistical test showed that significant correlation between knowledge and attitude with nutritional status of the children. That significant correlation KADARZI, continiously child weighing, to provide the exclusive breastfeeding and used of iodine salt with nutritional status of the children. The finding to do the socialization evenly about the KADARZI and the indicator of behavior to the society in order to prevent and minimize the nutrition problem for the child. Keyword: Nutritional Status, Children, KADARZI